PENGURUSAN JENAZAH COVID-19 DALAM PANDANGAN MEDIS DAN ISLAM - Hidayat, Ahmad; Masitoh, Imas; Irodat, Ahsan; Slamet, Hasan; Meliawati, Meliawati (Ta'dibiya, 2021)
The Covid-19 issue is a dangerous global disease that cannot be avoided, including deaths from the outbreak.However, in this study, he wants to explain how his death should get a decent position like death in general.Thisresearch is a qualitative research. The formulation of this research is: (1) How to take care of the corpse in generalaccording to Islam (2) How to manage the COVID-19 body according to the medical (3) How to manage theCOVID-19 body according to Islam.This research method uses content analysis research methods. for collectingdata, researchers used the method of interview, observation, based on exposure to data on research findings codedby the management of the bodies of COVID-19 in Islamic and medical viewpoints, it can be concluded that themanagement of the corpse is Fardu Kifayah by bathing, kafaning, tithing, and burying, according to Islamic andmedical views. the method prescribed by Islamic law.Thus, handling the bodies of Muslims infected with COVID19, must pay attention to the provisions of the shari'ah and the implementation of handling the bodies must meet theprovisions in the Standard Operating Procedures (SOP) of the medical party